Preparation and characterization of pvc based polymer electrolytes for proton batteries / Siti Khatijah Deraman - Deraman, Siti Khatijah (2014)
Searching a new material for the development of proton conducting polymer electrolytes that can be used in protonic electrochemical cells is the focus of this research study. In this study, the proton conducting polymer electrolytes were prepared by solution cast technique. Poly (vinyl chloride) PVC is used as the polymer host, ammonium triflate (NH₄CF₃S0₃) as the doping salt and ethylene carbonate (EC) and butyltrimethyl ammonium bis trifluoromethyl sulfonyl imide (Bu₃MeNTf₂N) is used as the plasticizers. Characterization techniques of EIS, XRD, FTIR, FESEM, DSC, TGA, transference number and linear sweep voltammetry measurements were used to study the properties of the PVC based proton conducting polymer electrolytes. Pure PVC exhibits room temperature ionic conductivity of 1.55 x 10¯¹⁰ S cm⁻¹. Various combinations of PVC and NH₄CF₃S0₃ compositions were attempted and the highest conductivity achieved was 2.50 x 10¯⁷S cm⁻¹ when 30 wt. % NH₄CF₃S0₃ (A4) was incorporated into PVC which is an increase of about three orders of magnitude, The increase in conductivity with addition of NH₄CF₃S0₃ is attributed to increase in number of mobile ions and decrease in crystallinity of the films as shown by XRD, FESEM and DSC results. A further increase in ionic conductivity is observed when the polymer-salt electrolyte with the highest conductivity (A4) was added with plasticizers EC and BU₃MeNTf₂N. The highest ionic conductivity achieved was 3.06 x 10-5 S cm-1when 5 wt. % of EC (B1) was incorporated to the A4 polymer electrolyte. When 15 wt. % BU₃MeNTf₂N (C3) was added to the A4 polymer electrolyte, the highest ionic conductivity achieved was 1.56 x 10⁻⁴ S cm⁻¹.Temperature dependence of conductivity study showed that conductivity increased with temperature and is found to obey the Arrhenius relationship. XRD studies showed that amorphous PVC becomes largely amorphous in nature upon addition of NH₄CF₃S0₃. Largely amorphous in nature is also obtained upon addition of EC and BU₃MeNTf₂N to PVC- NH₄CF₃S0₃. The degree of crystallinity, Xc is obtained by DSC and showed that the plasticized system has lower fraction of crystallinity compared to the salted systems with BU₃MeNTf₂N plasticized system having concentration of 15 wt. % (C3) having the least crystallinity. The transference number of this electrolyte is found to be 0.82 while its electrochemical window stability is 1.8 V. Electrochemical cells were fabricated using C3 electrolytes. The cells were discharged at different loads of 1.5 kΩ, 62 kΩ and 95 kΩ. The OCV of a cell based on the highest conducting electrolyte with configuration: Zn+ZnS0₄.7H₂O+PTFE I 85 wt. % (PVC-NH₄CF₃S0₃) +15 wt. % BU₃MeNTf₂N (C3) I MnO₂+PTFE is ~ 1.52 V while its discharge capacity is 0.55 mA h. The discharge performance of the cells showed that the protonic polymer electrolyte film proposed in this work has potential for application in protonic electrochemical cells for proton battery.